2017
DOI: 10.1016/j.joca.2017.07.015
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary weight loss with and without exercise on interstitial matrix turnover and tissue inflammation biomarkers in adults with knee osteoarthritis: the Intensive Diet and Exercise for Arthritis trial (IDEA)

Abstract: Summary Objective To examine the effects of dietary weight loss, with and without exercise, on selected soluble biomarkers in overweight and obese older adults with symptomatic knee OA. Design Blood samples were analyzed from 429 participants in the IDEA trial randomized to either an 18 month exericse control group (E), weight loss diet (D), or D+E. C1M, C2M, C3M and CRPM biomarkers and IL-6 were quantitated using ELISAs. Radiographic progression was defined as a decrease in joint space width of ≥ 0.7mm. St… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 23 publications
0
31
0
1
Order By: Relevance
“…Ultimately, we included 12 articles involving 57 study comparisons (Figure ). One study was reported in 2 different articles . We included both articles and counted them as 1 study with 2 study comparisons, as suggested in the Cochrane guidelines.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ultimately, we included 12 articles involving 57 study comparisons (Figure ). One study was reported in 2 different articles . We included both articles and counted them as 1 study with 2 study comparisons, as suggested in the Cochrane guidelines.…”
Section: Resultsmentioning
confidence: 99%
“…Biomarker samples were obtained at 4 to 24 weeks following the exercise therapy intervention in all the studies. Additionally, 3 studies reported in 4 articles included 1 additional follow‐up assessment at 18 months ; see Supplementary Table , available on the Arthritis Care & Research web site at http://onlinelibrary.wiley.com/doi/10.1002/acr.23786/abstract for a narrative synthesis of these results. However, we included the first available follow‐up time point in our analyses to allow for a more homogeneous time to follow‐up, ranging from 1 to 6 months across the included studies.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, one large study found decreased serum levels of CRPM, C1M, and C3M, suggesting beneficial effects of regular exercise on inflammation, bone, and cartilage health. 24 The current literature indicates that COMP is a dynamic BM, which may be suitable when assessing acute PA impact on joint tissue. However, COMP is not specific to cartilage, as COMP is present in tendinous tissue, 25 which is also largely stimulated during PA. Other dynamic and more specific BM, such as ARGS neoepitope of aggrecan (ARGS), 26 which may be useful for assessment of acute and long-term impact of PA still need evaluation.…”
Section: Resultsmentioning
confidence: 99%
“…However, these systemic biomarker changes were not associated with improvements in WOMAC pain or function despite signs of structural enhancement in the joint on MRI. 32…”
Section: The Benefits Of Weight Loss On Cartilagementioning
confidence: 99%